Detection of Metallo-Beta Lactamases Among Carbapenem-Resistant Pseudomonas aeruginosa - Farajzadeh Sheikh, Ahmad (Jundishapur J Microbiol, 2014)
BACKGROUND: Carbapenems are important drugs used for the treatment of Pseudomonas aeruginosa infections, however metallo-β-lactamases (MBL) are able to efficiently hydrolyze these classes of drugs. Immediate detection of the MBL-producing P. aeruginosa is necessary in order to accurately treat infections caused by this organism. OBJECTIVES: To determine the prevalence of MBL producing P. aeruginosa in burn and non-burn patients by two phenotypic tests and polymerase chain reaction (PCR) and to compare phenotypic tests with PCR. MATERIALS AND METHODS: A total of 223 non-duplicate strains of P. aeruginosa were collected from three teaching hospitals of Ahvaz, Iran. Antimicrobial susceptibility and minimum inhibitory concentrations (MICs) of carbapenems (imipenem, meropenem, doripenem and ertapenem) were determined by the Kirby-Bauer and E-test methods. Combined disk (CD) test, MBL E-test and PCR were performed for carbapenem-resistant P. aeruginosa isolates. RESULTS: Amongst all the P. aeruginosa isolates, 58.7% were resistant to imipenem while 31.8%, 13.5% and 74.4% were resistant to meropenem, doripenem and ertapenem, respectively. Amongst all the P. aeruginosa isolates, 44.4% were multidrug resistant and 13.45% were resistant to all of the carbapenems. The CD test with doripenem disk / 750 μg ethylene diamine tetra acetic acid (EDTA) had the highest efficiency compared to the other phenotypic tests. bla(IMP) and bla(VIM) genes were detected in 11.7% and 0.4% of isolates, respectively. bla(SPM) and bla(NDM) genes were not observed. CONCLUSIONS: Epidemiological and regional evaluation of MBL-producing P. aeruginosa through simple and inexpensive methods should be considered for effective treatment of carbapenem-resistant P. aeruginosa infections.